The Correlation between Grammar and Writing Achievement of EFL Sophomore Students at STKIP PGRI Pasuruan, Indonesia - Lestari Setyowati; Dita Dwi Hardiastikna (Universitas PGRI Madiun, 2019)
The purpose of this study is to know whether there is a significant correlation between students’ grammar mastery and their ability in writing. This research was conducted using quantitative method by using correlational research design. The target population of this research was all fourth semester students of English Education Study Program at Teachers Training and Education (STKIP) PGRI Pasuruan in academic year 2017/2018. The researcher used test and scoring guide as the instruments of this study. In collecting the data, the researcher conducted the writing test and the grammar test. The finding shows that there is no correlation between students’ writing ability and their grammar mastery for the fourth semester students of English Education Study Program at STKIP PGRI Pasuruan in academic year 2017/2018. The null hypothesis is not rejected because the significant value is 0.876 ≥ 0.05.